PEMANFAATAN MEDIA KARTU KUARTET DALAM MENINGKATKAN KETERAMPILAN KOMUNIKASI EFEKTIF DALAM PEMBELAJARAN KERAGAMAN BUDAYA SISWA KELAS 5 SEKOLAH DASAR - Evi Lutfiah; Herlyna Desi Riana; Neng Ira Sonia; Atikaharni, Wulan; Galih Dani Septyan Rahayu (JURNAL ILMIAH EDUNOMIKA, 2025)
Learning in the era of globalization today demands mastery of effective communication skills as part of 21st-century competencies, especially in the context of multicultural education. The use of innovative media such as quartet cards is expected to increase student participation, especially among previously passive students, and to develop effective communication skills. This study aims to describe the use of quartet cards as a medium to enhance the effective communication skills of fifth-grade elementary school students in cultural diversity learning. The method used is a descriptive quantitative approach that involves observing students and using an observation sheet with eight indicators of effective communication, which have been checked for accuracy and consistency through Corrected Item-Total Correlation and Cronbach’s Alpha analysis. The subjects of the study were 30 fifth-grade students from SDN Tonjong, Rongga District. Data were analyzed using validity tests, reliability tests, and descriptive statistics to assess the improvement in students' communication skills. The research results show that all indicators have a correlation value > 0.3 and reliable instruments (α > 0.7). The implementation of kuartet card media can encourage students to actively discuss, express opinions, listen effectively, and collaborate in groups, which makes the classroom atmosphere more interactive and inclusive and increases student participation, especially those who were initially passive. The conclusion of this research states that the quartets card media is an effective innovation in developing the effective communication skills of fifth-grade elementary school students in cultural diversity learning while also supporting the achievement of 21st-century competencies.